Biotransformation of Abiraterone Into Five Characteristic Metabolites by the Rat Gut Microbiota and Liver Microsomes - Keranmu, Adili; Yang, Fei-Ya; Wahafu, Wasilijiang; Han, Su-Jun; Yang, Guo-Sheng; Xing, Nian-Zeng (Frontiers in Oncology, 2022)
It is well known that the role of gut microbiota in drug metabolism, especially in oral difficult absorbable drugs. Understanding the gut microbiota could enable us to understand drugs in new ways. The purpose of the study was to investigate explore the metabolites of the anti-prostate cancer drug Abiraterone by examining gut microbiota metabolism and hepatic metabolism in vitro. In this study, five metabolites (M1, M2, M3, M4 and M5) of Abiraterone were discovered using LC/MSn-IT-TOF. Four isomeric metabolites M1-M4 were found in liver microsome. M5 was found in the intestinal contents of Sprague-Dawley rats with a molecular weight of 388.31. Among them, M4 was found to be Abiraterone N-Oxide by comparison with the standard sample. After further comparing the metabolic behavior of Abiraterone in rat gut microbiota and liver microsomes, we delineated the possible metabolic pathways of Abiraterone. In conclusion, Abiraterone is metabolized specifically in liver microsomes and gut microbiota. This study can provide a theoretical basis for elucidating the metabolic mechanism of Abiraterone and guide its rational application in clinic.